An Extended Approach to E-Inclusion and its Implications for Romania - Viorel Niţă (Romanian Journal of European Affairs, 2011)
Depending on the existing social patterns and trends, development of information society creates new opportunities and risks and restructures the established areas of public policy. For example, e-inclusion becomes more and more today’s predominant form of social inclusion. Despite the diversity of approaches developed, its intrinsic multi-dimension nature and the challenges posed by the continuous evolution of global digital technologies and networks make e-inclusion a problematic scientific and political concept. This article proposes an extended approach to e-inclusion, seen as the cumulative result of three interlocking contributors - i) global evolution of digital technologies and networks, ii) the levels of ICT access, usage and skills and iii) the existing social structures - and examine its policy implications for Romania. An important conclusion arises from this exploration: Romania is poorly prepared to cope with e-inclusion challenges. The country’s relatively incipient stage of information society development and its serious social problems and the emergence of new forms of digital divide demand a holistic policy response capable of coherently capturing and tackling all factors of e-inclusion, beyond the conventional fragmentation of public policy areas. Without it, social inclusion process will be hindered and Romania will not fully reap the social and economic benefits of information society.